Structured photoionization continuum of superheated cesium vapor. (8th July 2015) - Pichler, G; Makdisi, Y; Kokaj, J; Thomas, N; Mathew, J
Abstract: We studied the absorption spectrum of dense cesium vapor in an all-sapphire cell with a special emphasis on the highly structured photoionization continuum. This continuum appears to be composed of atomic and molecular contributions which can be separated by means of additional superheating of the cesium vapor in the sapphire cell. This was possible due to the small amount of cesium filling which completely evaporated at a temperature of around 450 °C. This enabled the overheating of cesium dimers which greatly reduced its concentration at a temperature of 900 °C, leaving almost pure atomic Cs vapor. The analysis of the thermal destruction indicated that the highly structured molecular component of the photoionization continuum can be entirely attributed to cesium dimers. We discuss the possible origin of the structured photoionization continuum as stemming from the absorption process from the ground state of the Cs2 molecule to the doubly excited Cs2 ** molecule located above Cs2 + molecular ionization limit. The corresponding potential curves are subjected to mutual interactions and autoionization.